The relationship between frailty in older adults and anxiety and depression in china: propensity score matching and network analysis - Li, Yinglin; Zhao, Ling; Lin, Doudou; Wang, Xinmei; Zhang, Chunlong; Zhou, Jiali; Cai, Zhongxiang (Frontiers in Psychiatry, 2025)
ObjectiveAnxiety and depression are common mental disorders in the elderly. Concurrent frailty may lead to worse clinical outcomes. This study examined the network structures of anxiety and depression in frail and non-frail older adults.MethodsThe Center for Epidemiologic Studies Depression Scale-10 (CESD-10) and the Generalized Anxiety Disorder Scale-7 (GAD-7) were used to measure depressive and anxiety symptoms, respectively. Following propensity score matching (PSM), 877 frail elderly individuals were matched with 877 non-frail elderly individuals. Central (influential) and bridge symptoms were estimated using the expected influence (EI) and bridge expected influence (bridge EI), respectively. Network stability was assessed using the case-dropping bootstrap method.ResultsBased on the NCT results, there were no significant differences in the comparison of the network models between the non-frailty group and the frailty group in terms of global strength (7.175 vs. 7.136, S = 0.039, P = 0.802) and network structure (M = 0.137, P = 0.703). There were also no significant differences in edge weights between the networks of the two groups (P > 0.05).ConclusionNCT results showed no significant difference in the network structure of anxiety and depression between frail elderly and control groups. A slight decrease in network strength was observed in non-frail elderly but was not statistically significant. Both groups showed similar characteristics in bridging symptoms, central symptoms, overall strength, and network structure. Interventions for anxiety and depression are equally beneficial for both frail and non-frail elderly.